UU No. 16 Tahun 2001 tentang Yayasan; Telaah Kebijakan Pendidikan Dasar dan Menengah Terkait Eksistensi Madrasah Swasta dan Yayasan - Erlan Muliadi; Ulyan Nasri (Institut Agama Islam Hamzanwadi Pancor, 2023)
This research investigates the impact of Law No. 16 of 2001 on foundations in the context of primary and secondary education, particularly its influence on private madrasahs in Indonesia. The law establishes the legal framework for foundations, which play a pivotal role in shaping the country's education system. Employing a library research approach, this study gathers, analyzes, and synthesizes data from diverse literature sources, legal regulations, and prior research. The study underscores several critical aspects. First, it delves into the legal framework provided by Law No. 16 of 2001 for foundation establishment and operation, which is vital as many private madrasahs and educational institutions operate under the aegis of foundations. This framework encompasses prerequisites for founding, organizational structure, financial management, and governance. Second, it examines the impact of the law on private madrasahs' existence, funding, and oversight, addressing whether it has catalyzed their growth or posed unique challenges to them. Third, the research explores the contributions of foundations not only to private madrasahs but also to various primary and secondary educational institutions, focusing on their role in enhancing educational access and quality. Lastly, it identifies the obstacles and challenges faced by foundations and private madrasahs in implementing Law No. 16 of 2001, including financial issues, educator qualifications, and oversight. This research promises to provide a comprehensive understanding of Law No. 16 of 2001's role in the context of primary and secondary education in Indonesia, serving as a foundation for policy enhancements.